Pediatric Patient with Ischemic Stroke: Initial Approach and Early Management - Jozef Klučka; Eva Klabusayová; Tereza Musilová; Tereza Kramplová; Tamara Skříšovská; Milan Kratochvíl; Martina Kosinová; Ondřej Horák; Hana Ošlejšková; Petr Jabandžiev; Petr Štourač (MDPI AG, 2021)
Acute Ischemic Stroke (AIS) in children is an acute neurologic emergency associated with significant morbidity and mortality. Although the incidence of AIS in pediatric patients is considerably lower than in adults, the overall cumulative negative impact of the quality of life could be even higher in children. The age-related variable clinical presentation could result in a delay in diagnosis and could negatively influence the overall outcome. The early management should be based on early recognition, acute transfer to pediatric AIS centre, standardised approach (ABCDE), early neurologic examination together with neuroimaging (preferable Magnetic Resonance Imaging-MRI). The treatment is based on supportive therapy (normoxemia, normocapnia, normotension and normoglycemia) in combination with intravenous/intraarterial thrombolytic therapy and/or mechanical thrombectomy in selected cases. Pediatric stroke centres, together with the implementation of local stroke management protocols, could further improve the outcome of pediatric patients with AIS.